Diagnostic performance of circulating exosomes in human cancer: A meta‐analysis. Issue 8 (20th April 2020) - Guo, Dongming; Yuan, Jinpeng; Xie, Aosi; Lin, Zeyin; Li, Xinxin; Chen, Juntian
Abstract: Background: Cancer has become a public health problem with high morbidity and mortality. Recent publications have shown that exosomes can be used as potential diagnostic biomarkers of cancer. However, the diagnostic accuracy and reliability of circulating exosomes remain unclear. The present meta‐analysis was conducted to comprehensively summarize the overall diagnostic performance of circulating exosomes for cancer. Methods: Eligible studies published up to June 27, 2019, on PubMed, Embase, and Cochrane Library were selected for the meta‐analysis. All statistical analyses were performed by STATA 15.1 statistical software and Meta‐DiSc 1.4. Quality Assessment for Studies of Diagnostic Accuracy 2 tool was used to access the quality of included studies. A bivariate mixed‐effects model was applied to calculate the diagnostic indexes from included studies. Results: A total of 5924 participants comprising 3161 cases and 2763 controls from 42 eligible studies were analyzed. The pooled sensitivity, specificity, positive likelihood ratio, negative likelihood ratio, diagnostic odds ratio, and the area under the curve with 95% confidence intervals (95% CI) were as follows: 0.79 (0.75‐0.82), 0.81 (0.78‐0.84), 4.1 (3.5‐4.8), 0.26 (0.22‐0.31), 16 (12‐21), and 0.87 (0.84‐0.89), respectively. Sensitivity analysis suggested no study exclusively contributed to the heterogeneity, and Deeks' funnel plot asymmetry test indicated no potential publication bias ( P  = .09). Conclusions: The meta‐analysis indicated that circulating exosomes could serve as effective and minimally invasive biomarkers for diagnosis of cancer, especially in patients with hepatocellular carcinoma or ovarian cancer, serum‐based samples and exosomal proteins.